DESIGN AND MANUFACTURING OF JIG FOR ELBOW - Mr. Javed Gulab Mulla; Aditi Gajanan Surwase; Nayna Raju Matka; Yuvraj Udaysingh Gautam (International Journal of Innovations in Engineering Research and Technology, 2026)
This work focuses on the design and manufacturing of a jig for an elbow component used in piping systems. The main objective is to improve production efficiency, accuracy, and repeatability during machining operations such as drilling and positioning. The sponsored company is engaged in machining of pipe Elbow casting. The elbow component has a complex geometry, which makes it difficult to hold firmly using conventional methods. To overcome this problem, a specially designed jig is developed to properly locate and clamp the component. The jig is designed based on the principles of locating, clamping, and guiding to ensure precise machining and reduced setup time. Proper selection of materials and manufacturing processes is considered to achieve durability and cost-effectiveness. The use of the jig minimizes human error, increases productivity, and ensures uniform quality in mass production. The final outcome of this work demonstrates that the designed jig significantly enhances machining accuracy and reduces production time for the elbow component, making it suitable for industrial applications.